2015
DOI: 10.1158/1078-0432.ccr-13-0645
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Regulation and Targeting of Kinetochore–Microtubule Attachment in Cancer

Abstract: Kinetochores are large protein structures assembled on centromeric DNA during mitosis that bind to microtubules of the mitotic spindle to orchestrate and power chromosome movements. Deregulation of kinetochore-microtubule (KT-MT) attachments has been implicated in driving chromosome instability and cancer evolution; however, the nature and source of KT-MT attachment defects in cancer cells remain largely unknown. Here we highlight recent findings suggesting that oncogene-driven changes in kinetochore regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 66 publications
0
21
0
1
Order By: Relevance
“…In contrast, we observed that in ~60% of GSCs, Ras-transformed cells, and HeLa cells its GLEBs domain becomes essential for viability to promote kinetochore-microtubule attachment (17). Mechanistic experiments demonstrated that oncogenic Ras signaling triggers alterations in kinetochore regulation resulting in added GLEBs domain requirement and the primary reason we observe differentially sensitivity to BUB1B knockdown (17,24). …”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In contrast, we observed that in ~60% of GSCs, Ras-transformed cells, and HeLa cells its GLEBs domain becomes essential for viability to promote kinetochore-microtubule attachment (17). Mechanistic experiments demonstrated that oncogenic Ras signaling triggers alterations in kinetochore regulation resulting in added GLEBs domain requirement and the primary reason we observe differentially sensitivity to BUB1B knockdown (17,24). …”
Section: Introductionmentioning
confidence: 78%
“…To this end, we analyzed the RNA-seq profiles of 18 GSCs as well as astrocyte and neural progenitor cells, classifying them by BUB1B R/S status. BUB1B R/S status was determined by sensitivity to LV-shBUB1B and/or measurement of inter-kinetochore distance at metaphase (17,24) (Supplementary Table S1 and Supplementary Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of SAC function has been attributed to CIN and aneuploidy in several cancers (Kops et al . 2005, Herman et al . 2015).…”
Section: Unexplored Arenas For Potential Development Of Novel Cancmentioning
confidence: 99%